2021
DOI: 10.24135/afl.v10i.342
|View full text |Cite
|
Sign up to set email alerts
|

Are Stablecoins Safe Havens for Traditional Cryptocurrencies? An Empirical Study during the COVID-19 Pandemic

Abstract: We investigate whether stablecoins are safe havens for traditional cryptocurrencies with fresh evidence from the recent crisis period of the COVID-19 pandemic. Our results support the safe-haven properties of Tether for both before and during the pandemic. For Digix, a gold-backed stablecoin with relatively small market capitalization, we find a change in characteristics before and during the pandemic, but do not find statistically significant evidence for its safe-haven properties. Furthermore, we document th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The examination of Jeger et al (2020) on stablecoins found that Tether and DAI furnished liquidity and steadiness during the downturn of the cryptocurrencies market in 2020 during the outbreak of COVID-19. Xie et al (2021) agree with Conlon et al (2020). Their findings provide evidence for the safe-haven characteristics of Tether, both prior to and amidst the outbreak of COVID-19.…”
Section: Literature Reviewsupporting
confidence: 58%
“…The examination of Jeger et al (2020) on stablecoins found that Tether and DAI furnished liquidity and steadiness during the downturn of the cryptocurrencies market in 2020 during the outbreak of COVID-19. Xie et al (2021) agree with Conlon et al (2020). Their findings provide evidence for the safe-haven characteristics of Tether, both prior to and amidst the outbreak of COVID-19.…”
Section: Literature Reviewsupporting
confidence: 58%
“…This research is the first of its kind that explores the moderating impact of geopolitical risk in an integrated framework of the COVID 19 uncertainty, oil prices, energy prices and renewable energy prices. The extant literature has failed to investigate the moderating impact of geopolitical risk on the pandemic uncertainty and its impact on renewable stock prices (Xie et al, 2021). Such exercises will help to broaden the scope of the policy implications on the path of recovery in the post-pandemic situation and reforms on investment in renewable energy stocks.…”
Section: Background Literaturementioning
confidence: 99%
“…The most discussed safe-haven assets in the extant literature include gold ( Baur and Lucey, 2010 ; Shahzad et al, 2020 ) and cryptocurrencies (D. G. Baur and Hoang, 2021 ; Dwita Mariana, Ekaputra and Husodo, 2021 ; Goodell and Goutte, 2020 ; Rubbaniy et al, 2021a , Rubbaniy et al, 2021b , Rubbaniy et al, 2021c ; Xie et al, 2021 ). Some existing studies ( Bodie and Rosansky, 1980 ; Conover et al, 2009 ; Daskalaki and Skiadopoulos, 2011 ; Daskalaki et al, 2017 ; Ji et al, 2020 ) support the view that equity investors can achieve diversification benefits by including commodities in their portfolios.…”
Section: Introductionmentioning
confidence: 99%